2022
DOI: 10.1093/nsr/nwac144
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen cleavage and hydrogenation to ammonia with a uranium complex

Abstract: The Haber–Bosch process produces ammonia (NH3) from dinitrogen (N2) and dihydrogen (H2), but requires high temperature and pressure. Before iron-based catalysts were exploited in the current industrial Haber–Bosch process, uranium-based materials served as effective catalysts for production of NH3 from N2. Although some molecular uranium complexes are known to be capable of combining with N2, further hydrogenation with H2 forming NH3 has not been reported to date. Here, we describe the first example of N2 clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Particularly, due to the synergistic effects from different metal centers, the clusters with M-M bonds have great potential in the activation and conversion of N 2 to N-containing organic compounds. [72][73][74][75] In conclusion, we have highlighted recent advances in the construction of d-f heterometallic molecular clusters with M-M bonds. We hope that this review will attract more chemists to this burgeoning but challenging field and stimulate the steady developments and breakthroughs in future.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, due to the synergistic effects from different metal centers, the clusters with M-M bonds have great potential in the activation and conversion of N 2 to N-containing organic compounds. [72][73][74][75] In conclusion, we have highlighted recent advances in the construction of d-f heterometallic molecular clusters with M-M bonds. We hope that this review will attract more chemists to this burgeoning but challenging field and stimulate the steady developments and breakthroughs in future.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Xin, Zhu and co-workers also reported that the reduction of a U(IV) azide complex, supported by the (NNP 2 ) 2− ligand ( 5a ), with excess KC 8 under N 2 generates the trinuclear imido–nitride complex, [K 2 ((U(NNP 2 ) 2 (μ-NH) 3 (μ-N))] ( 5 ) (bottom, Scheme 3). 69 The molecular structure of 5 consists of three uranium centers that are bridged by three imido (NH) ligands, and one nitride (N 3− ) ligand with U–N nitride bond lengths which range from 2.204 to 2.218 Å. These distances are comparable to those reported for the U( iv )/U( vi ) tetranitride cluster 1 , and slightly longer than those found in the nitride bridged cluster, [(U IV Cp*(μ-I) 2 ) 3 (μ-N)], reported by Evans and co-workers (2.138(3)–2.157(3) Å).…”
Section: Actinide Nitride Complexes Derived From N2 Cleavagementioning
confidence: 99%
“…We have developed a phosphorus-substituted Tren ligand (a double layer N–P ligand), which contains three rigid N–P units. The P atoms in this ligand play important roles not only in the construction of heterometallic clusters with M–M bonds but also in the activation of small molecules. Here, we report the photolysis, thermolysis, and reduction of the uranium azide complex supported by this double layer N–P ligand.…”
Section: Introductionmentioning
confidence: 97%